2018
DOI: 10.1182/blood-2017-12-823369
|View full text |Cite
|
Sign up to set email alerts
|

Platelets play an essential role in murine lung development through Clec-2/podoplanin interaction

Abstract: Platelets participate in not only thrombosis and hemostasis but also other pathophysiological processes, including tumor metastasis and inflammation. However, the putative role of platelets in the development of solid organs has not yet been described. Here, we report that platelets regulate lung development through the interaction between the platelet-activation receptor, C-type lectin-like receptor-2 (Clec-2; encoded by ), and its ligand, podoplanin, a membrane protein. Clec-2 deletion in mouse platelets led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 52 publications
2
35
0
Order By: Relevance
“…Recently, it was demonstrated that the interaction between platelet CLEC-2 receptor and lymphatic endothelial cell podoplanin regulates murine lung development. This direct interaction leads through platelet activation to TGF-␤1 release, which is necessary for normal lung cell differentiation during late embryonic development (44). Our in vitro data provide additional evidence of CLEC-2-mediated TGF-␤1 release from platelets.…”
Section: Discussionsupporting
confidence: 52%
“…Recently, it was demonstrated that the interaction between platelet CLEC-2 receptor and lymphatic endothelial cell podoplanin regulates murine lung development. This direct interaction leads through platelet activation to TGF-␤1 release, which is necessary for normal lung cell differentiation during late embryonic development (44). Our in vitro data provide additional evidence of CLEC-2-mediated TGF-␤1 release from platelets.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, the blood cell count of adult mice treated with moderate neonatal hyperoxia differed from untreated mice with particular increase in platelets. Murine platelets are mainly generated from megakaryocytes in the lung tissue [48] and are able to support the lung development [49]. Therefore, its increase could suggest higher activity of cellular processes compensating for the oxygen-mediated damages, but the potential role of platelets in the reduction of oxygen-mediated damages in newborn lungs is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…ner (56). The degree of blood-lymphatic mixing is reduced in mice with a targeted deletion of CLEC-2 in the megakaryocyte/platelet lineage (PF4-Cre.Clec-1b fl/fl ), and the mice are viable, albeit with a 30% reduction in platelet count.…”
Section: Gpvimentioning
confidence: 99%